Neoadjuvant chemoimmunotherapy in locally advanced gastric or gastroesophageal junction adenocarcinoma - Liu, Xiao; Ma, Baozhen; Zhao, Lingdi (Frontiers in Oncology, 2024)
Patients suffering from locally advanced gastric or gastroesophageal junction adenocarcinoma often face a high postoperative recurrence rate. Despite aggressive treatment, less than 50% survive beyond five years. Ongoing clinical studies are exploring ways to prolong patient survival, revealing that perioperative chemotherapy can extend both the period of recurrence-free survival and overall survival for this group of patients. Currently, combining chemotherapy and immune checkpoint inhibitors has become a critical treatment approach for advanced gastric or gastroesophageal junction adenocarcinoma. However, the effectiveness of this approach in locally advanced patients remains unverified. This article delves into the latest research concerning the use of perioperative chemotherapy coupled with immune checkpoint inhibitors in locally advanced gastric or gastroesophageal junction adenocarcinoma treatment, and highlights prospective challenges and discusses how to best identify patients who may benefit from combined chemotherapy and immune checkpoint inhibitor therapy.